2018
DOI: 10.2174/1381612824666180515123543
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated C-phycocyanin Liposome for Extending the Neuroprotective Time Window Against Ischemic Brain Stroke

Abstract: The time window for neuroprotection during ischemic brain stroke is short, and hence, development of neuroprotectants is critical to extend this time window. This study sought to verify if muco-adhesive chitosan coating improves the neuroprotective potential of the pre-proven C-Phycocyanin-pertaining liposome (C-Pc liposome). The use of chitosan-coated liposomes extended the neuroprotective time window by 6 h after occlusion, and further improved the neuroprotection efficiency of the C-Pc liposome in a rat Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Other authors corroborated the anti-apoptotic action of C-PC on rat primary astrocytes during trophic factor deprivation, an effect partially explained by its antioxidant activity [ 121 ]. Chitosan-coated C-PC liposomes also protected rat primary astrocytes from H 2 O 2 toxicity, while decreasing the expression of TNF-α and inducing the phosphacan and neurocan genes, both glia scar-associated proteoglycans [ 122 ]. Previously, it has been observed that these C-PC encapsulated liposomes protected the murine Neuro2A cell line from H 2 O 2 toxicity [ 123 ].…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors corroborated the anti-apoptotic action of C-PC on rat primary astrocytes during trophic factor deprivation, an effect partially explained by its antioxidant activity [ 121 ]. Chitosan-coated C-PC liposomes also protected rat primary astrocytes from H 2 O 2 toxicity, while decreasing the expression of TNF-α and inducing the phosphacan and neurocan genes, both glia scar-associated proteoglycans [ 122 ]. Previously, it has been observed that these C-PC encapsulated liposomes protected the murine Neuro2A cell line from H 2 O 2 toxicity [ 123 ].…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
“…As chitosan material has been suggested to be a preferred system for delivery to the olfactory bulb (as opposed to the nasopharynx) through nasal mucin adhesion [ 128 ], a follow-up study tested the ability of cholesterol C-PC liposomes coated with chitosan for improving the neuroprotective action of the encapsulated biliprotein in IS. When applied intranasally at 0.5 mg/mL (around 13.9 µg/kg considering a 300 g rat) 6 h after stroke, chitosan-coated cholesterol C-PC liposomes significantly reduced the infarct volume (64.9% relative to the vehicle ischemic group) as compared to the non-chitosan C-PC particles (88.6%), despite the fact that the C-PC dose was eight-times smaller due to the presence of chitosan in the nanoformulation [ 122 ].…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
“…Polysaccharides not only act as drug carriers but also enhance the neuroprotective capacity of the carriers. Chung et al ( 2018 ) demonstrated that adherent chitosan coating enhances the neuroprotective potential of c-phycocyanin modified liposomes (C-Pc liposomes). The application of chitosan-coated liposomes prolonged the neuroprotective time window of 6 h in a rat middle cerebral artery occlusion (MCAO) model, further improving the neuroprotective efficiency of C-Pc liposomes.…”
Section: Nanomaterials-based Drug Deliverymentioning
confidence: 99%
“…The application of chitosan-coated liposomes prolonged the neuroprotective time window of 6 h in a rat middle cerebral artery occlusion (MCAO) model, further improving the neuroprotective efficiency of C-Pc liposomes. And in cultured astrocytes, chitosan-coated C-Pc liposomes exhibited antioxidant activity but no cytotoxicity (Chung et al, 2018 ).…”
Section: Nanomaterials-based Drug Deliverymentioning
confidence: 99%
“…Phycocyanin, a blue photosynthetic pigment deriving from Spirulina and Cyanobacteria cells, has been used as a food additive in many products such as soft drinks, candies, chewing gum, and ice cream [ 7 ]. Meanwhile, phycocyanin is a type of functional factor that has been proven to possess therapeutic properties, including anti-inflammatory [ 8 ], antioxidant [ 9 ], antineoplastic [ 10 ], neuroprotective [ 11 ], and hepatoprotective [ 12 ] activities. Unlike most chemical drugs, phycocyanin is verified to have few or no toxic side effects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%